TRANSFORMASI PEMBELAJARAN FISIKA DASAR DI MASA PANDEMI - Syafi’i, Muhammad (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
The covid-19 pandemic demands changes to the learning system. Changes in the learning system cause learning activities, media, assignments, and learning assessments to undergo adjustments to be carried out online. Fundamental physics is one of the courses in several study programs which must also be adjusted according to its implementation. Currently, many learning platforms are available. The purpose of this research is to examine the learning platforms that are often used for Fundamental Physics courses. This type of research is literature study research. The data obtained is secondary data from published articles. The results of this study indicate that the learning platforms that are most often used are Moodle, Edmodo, and Google Classroom. The platforms for virtual labor are macromedia and Phet simulation. Ease of use is the main basis for selecting the platform by educators, besides that the existence of discussion and conference services is an added values. As for virtual labor, Phet simulation is considered more practical because it can use existing simulations, it's just that not all the experimental forms that educators want can be available in Phet simulation